High-Order-Tilted Fiber Bragg Gratings With Superposed Refractive Index Modulation - Xuan-Yu Zhang; Chao Chen; Yong-Sen Yu; Wei-Hua Wei; Qi Guo; Yong-Yi Chen; Xing Zhang; Li Qin; Yong-Qiang Ning; Hong-Bo Sun (IEEE Photonics Journal)
A high-order-tilted fiber Bragg gratings (HO-TFBG) with superposed refractive index (RI) modulation written by a femtosecond laser and a phase mask has been demonstrated. The superposed grating structure is realized by the combined action of the pure ±1 order pulses interference and the heat accumulation effect of ±1 order and zero-order pulses. For the phase mask with the pitch of 3.33 μm, there are 11 groups of high-order Bragg resonance and cladding mode resonances sets in the wavelength range of 600–1700 nm, the information carried by which is doubled compared to the HO-TFBG written by pure two beams interference. It demonstrates that the sensitivities of the cladding mode resonances sets to surrounding RI, axial strain and temperature decrease with the increase of the grating order.